Peran Adam Malik dalam Perkembangan Politik Indonesia pada Awal Kemerdekaan - Purba, Tifany Azriel Hasyim (Laboratorium Sejarah, Departement Ilmu Sejarah, Fakultas Ilmu Budaya, Universitas Andalas, 2024)
Adam Malik was a pivotal figure in Indonesia's political history at the dawn of independence. As a journalist, diplomat, and politician, Malik played a key role in significant events that shaped the modern Indonesian state. This article explores Adam Malik's contributions to Indonesia's political development during the early independence period, highlighting his role in international diplomacy, national political movements, and efforts to defend Indonesia's independence from internal and external threats. This research employs a historical approach, examining various primary and secondary sources to provide a comprehensive picture of Adam Malik's influence on Indonesian politics.